Lipid environment induces ER stress, TXNIP expression and inflammation in immune cells of individuals with type 2 diabetes - Szpigel, Anaïs; Hainault, Isabelle; Carlier, Aurélie; Venteclef, Nicolas; Batto, Anne-Françoise; Hajduch, Eric; Bernard, Catherine; Ktorza, Alain; Gautier, Jean-François; Ferré, Pascal; Bourron, Olivier; Foufelle, Fabienne (Diabetologia, 2018)
Aims/hypothesis Obesity and type 2 diabetes are concomitant with low-grade inflammation affecting insulin sensitivity and insulin secretion. Recently, the thioredoxin interacting protein (TXNIP) has been implicated in the activation process of the NOD-like receptor family, pyrin domain containing 3 (NLRP3) inflammasome. In this study, we aim to determine whether the expression of TXNIP is altered in the circulating immune cells of individuals with type 2 vs type 1 diabetes and whether this can be related to specific causes and consequences of inflammation. Methods The expression of TXNIP, inflammatory markers, markers of the unfolded protein response (UPR) to endoplasmic reticulum (ER) stress and enzymes involved in sphingolipid metabolism was quantified by quantitative reverse transcription real-time PCR (qRT-PCR) in peripheral blood mononuclear cells (PBMCs) of 13 non-diabetic individuals, 23 individuals with type 1 diabetes and 81 with type 2 diabetes. A lipidomic analysis on the plasma of 13 non-diabetic individuals, 35 individuals with type 1 diabetes and 94 with type 2 diabetes was performed. The effects of ER stress or of specific lipids on TXNIP and inflammatory marker expression were analysed in human monocyte-derived macrophages (HMDMs) and THP-1 cells. Results The expression of TXNIP and inflammatory and UPR markers was increased in the PBMCs of individuals with type 2 diabetes when compared with non-diabetic individuals or individuals with type 1 diabetes. TXNIP expression was significantly correlated with plasma fasting glucose, plasma triacylglycerol concentrations and specific UPR markers. Induction of ER stress in THP-1 cells or cultured HMDMs led to increased expression of UPR markers, TXNIP, NLRP3 and IL-1β. Conversely, a chemical chaperone reduced the expression of UPR markers and TXNIP in PBMCs of individuals with type 2 diabetes. The lipidomic plasma analysis revealed an increased concentration of saturated dihydroceramide and sphingomyelin in individuals with type 2 diabetes when compared with non-diabetic individuals and individuals with type 1 diabetes. In addition, the expression of specific enzymes of sphingolipid metabolism, dihydroceramide desaturase 1 and sphingomyelin synthase 1, was increased in the PBMCs of individuals with type 2 diabetes. Palmitate or C2 ceramide induced ER stress in macrophages as well as increased expression of TXNIP, NLRP3 and IL-1β. Conclusions/interpretation In individuals with type 2 diabetes, circulating immune cells display an inflammatory phenotype that can be linked to ER stress and TXNIP expression. Immune cell ER stress can in turn be linked to the specific exogenous and endogenous lipid environment found in type 2 diabetes.